Potent human glutaminyl cyclase inhibitors as potential anti-Alzheimer's agents: Structure-activity relationship study of Arg-mimetic region. Issue 5 (1st March 2018) - Ngo, Van T.H.; Hoang, Van-Hai; Tran, Phuong-Thao; Ann, Jihyae; Cui, Minghua; Park, Gyungseo; Choi, Sun; Lee, Jiyoun; Kim, Hee; Ha, Hee-Jin; Choi, Kwanghyun; Kim, Young-Ho; et al.
Graphical abstract: Abstract: Pyroglutamate-modified amyloid β peptides (pGlu-Aβ) are highly neurotoxic and promote the formation of amyloid plaques. The pGlu-Aβ peptides are generated by glutaminyl cyclase (QC), and recent clinical studies indicate that QC represents an alternative therapeutic target to treat Alzheimer's disease (AD). We have previously developed a series of QC inhibitors with an extended pharmacophoric scaffold, termed the Arg-mimetic D-region. In the present study, we focused on the structure activity relationship (SAR) of analogues with modifications in the D-region and evaluated their biological activity. Most compounds in this series exhibited potent activity in vitro, and our SAR analysis and the molecular docking studies identified compound202 as a potential candidate because it forms an additional hydrophobic interaction in the h QC active site. Overall, our study provides valuable insights into the Arg-mimetic pharmacophore that will guide the design of novel QC inhibitors as potential treatments for AD.